Meningkatkan Kinerja UMKM Melalui Literasi Keuangan, Inovasi Produk, Budaya Organisasi dan Kebijakan Pemerintah - Riyanti, Budi; Astuti, Erika Dwi (Peneliti.net, 2024)
The Covid-19 pandemic has dealt a major blow to all sectors, especially the business sector. Many companies went bankrupt and forced companies to lay off employees. As a result of the large number of layoffs, a new wave of MSMEs has emerged. The same thing happened in the city of Salatiga, there was a significant increase in both the number of MSMEs and the performance of MSMEs during the pandemic until now. This phenomenon is very interesting to research, where during the pandemic many MSMEs died and went bankrupt, but the opposite happened to Salatiga City MSMEs. The aim of this study is to analyze the factors that influence the performance of Salatiga City MSMEs. The population of this study is MSMEs in the city of Salatiga with a sample of 100 MSMEs. The data used is primary data with quantitative analysis techniques. Hypothesis testing uses multiple regression analysis. Data is processed using the Smart Partial Least Square (PLS) 3.0 program. The results of the study show that financial literacy, product innovation, organizational culture and government policy have a positive influence on the performance of MSMEs.